Studying the Efficiency of Balancing Pond Function in Sanitary Sewage Treatment Using the Activated Sludge Method (Case Study: Sewage Treatment Plant of Brigade 37) - Mohammad Hadi Fattahi; Mohammad Hosseini; Sohrab Karami (علوم و مهندسی آب و فاضلاب, 2021)
Aerobic biological treatment systems are very suitable for removing contaminants of organic matter in the sewage. Accordingly, the continuity of the inlet flow to the treatment plant, in design and exploitation of these processes, is necessary to consider. One of the differences between industrial and low population areas wastewater, such as military garrisons, and the Municipal sewage, is their volumetric fluctuations. These fluctuations may have a negative effect on the activated sludge process; thus the efficiency of using balancing pool in activated sludge systems has been analyzed in this research. Wastewater treatment process is based on biologically activated sludge method and extensive aeration. In this method, the raw wastewater is directed to the pumping station gravitationally. Results illustrated that, the inlet flow rate to the treatment plant, has high fluctuations from 0 to 40 (m3/hour) at different hours of the day due to the low population. Based on the samplings, it has been determined that the efficiency of activated sludge process in removing the parameters of BOD5, COD, TSS and ammonia during one week is averagely 61, 61, 68 and 24%, respectively. According to the sewage standards, this treated sewage is not suitable for injection into water wells or surface water or for reuse in agriculture. Whilst, using the balancing pond and controlling the inlet flow to the aeration pond at a rate of 12 cubic meters per hour, the removal efficiency of BOD5, COD, TSS and ammonia escalates averagely 90, 90, 89.19 and 81.59%, respectively during a week.